2017
DOI: 10.1016/j.bjorl.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Position statement of the Brazilian Academy of Rhinology on the use of antihistamines, antileukotrienes, and oral corticosteroids in the treatment of inflammatory sinonasal diseases

Abstract: There is support in the literature for the use of these drugs; however, final considerations about the role of each of them have been made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
1
0
1
Order By: Relevance
“…Together with LTRA, studies have shown benefits in improving sleep quality and in reducing nasal congestion and complications. 14,15 The efficacy of antihistamines is most often restricted by the sedation associated with it and is caused primarily by its inhibition of the central histamine neurons in the brain. 16 Bilastine was reported as the least sedative antihistamine by majority (41.55%) of the physician.…”
Section: Discussionmentioning
confidence: 99%
“…Together with LTRA, studies have shown benefits in improving sleep quality and in reducing nasal congestion and complications. 14,15 The efficacy of antihistamines is most often restricted by the sedation associated with it and is caused primarily by its inhibition of the central histamine neurons in the brain. 16 Bilastine was reported as the least sedative antihistamine by majority (41.55%) of the physician.…”
Section: Discussionmentioning
confidence: 99%
“…Однако результаты многочисленных исследова-ний в этой области показали их эффективность только при сопутствующем аллергическом рините [70].…”
Section: антигистаминная терапияunclassified